Making bombs for Hitler - Skrypuch, Marsha Forchuk (Scholastic Press, 2017)
In 1943 ten-year-old Lida is torn away from her home in the Ukraine, separated from her little sister Larissa, and sent to a slave labor camp in Germany, but when she is moved and set to making bombs she sees a way to strike back at the Nazis.